Effect of Particle Size on Structural, Physicochemical and Functional Properties of Highland Barley Bran - Tong WANG; Xueqing WANG; Yaning TIAN; Jingjing YANG; Bin DANG; Xiaogang SHEN; Fengzhong WANG; Lili WANG (Shipin gongye ke-ji)
In this study, airflow impact milling (AFIM) with different intensity was utilized to mill coarse highland barley bran (CHB) in order to investigate the effects of particle size on the structure, physicochemical, and functional characteristics of the bran. Medium highland barley bran (MHB) with an average particle size of 69.04 µm, fine highland barley bran (FHB) with a particle size of 58.85 µm, and ultrafine highland barley bran (UHB) with a particle size of 32.04 µm were obtained. These parameters of four samples were then analyzed in terms of particle size distribution, microstructure, physicochemical composition, pore characteristics, and functional properties. The results indicated that as the particle size of highland barley bran decreased, a portion of insoluble dietary fiber (IDF) transformed into soluble dietary fiber (SDF), leading to an increase in the proportion of SDF in the total dietary fiber from 7.18% (CHB) to 8.50% (UHB). Microscopic and pore characteristic studies revealed that with the reduction in particle size, the packing state of highland barley bran became more compact, and the micro-pores ranging from 50 nm to 10 µm gradually dominated the bran's pore structure, increasing from 31% in the CHB group to 69% in the UHB group. The changes in composition and structure of the bran influenced its water-holding capacity, oil-holding capacity, and other hydration properties. Compared to CHB, UHB exhibited a reduction of 21% in water-holding capacity and 7.64% in oil-holding capacity. In vitro glucose adsorption experiments demonstrated that as the particle size decreased, highland barley bran exhibited enhanced adsorption ability and inhibition of diffusion for high concentrations of glucose. In conclusion, airflow impact milling, a physical modification, effectively reduced the particle size distribution of highland barley bran and significantly altered its chemical composition, microstructure, pore structure, and particle packing state, thereby affecting its physicochemical and functional characteristics.